Revolutionizing Pesantren In The Society 5.0 Era: The Synergy Of Digitalization, Ai, And Smart Education Management - Sherli Ananda Calista (Proceeding of International Conference on Islamic Boarding School, 2025)
Pesantren, as a cornerstone of Islamic education, must adapt to the Society 5.0 era, where artificial intelligence (AI), digitalization, and smart education management redefine learning and institutional governance. This study examines the integration of AI and digitalization in pesantren, focusing on their impact on educational quality, operational efficiency, and long-term sustainability. Using a qualitative approach, the research explores existing digital transformation efforts, challenges faced by pesantren, and strategic frameworks for successful adaptation. The findings indicate that while digitalization enhances teaching methodologies, administrative management, and access to global knowledge, financial limitations, digital literacy gaps, and cultural resistance remain key obstacles. This study proposes a sustainable model for pesantren digital transformation, emphasizing AI-driven learning platforms, financial technology for waqf management, and digital literacy training for educators and students. These findings contribute to the discourse on Islamic education modernization, providing practical insights for policymakers, educators, and Islamic institutions to successfully navigate the Society 5.0 landscape.